UI/UX дизайн лендингових сторінок для благодійних зборів: ключові принципи та вплив на залучення донорів - Гавриш, Є. М. (ХНУРЕ, 2025)
This work is dedicated to the study of UI/UX design principles for landing pages used in charitable fundraising. The research emphasizes the importance of accessibility, financial transparency, emotional engagement, simplified navigation, and social media integration in attracting donors and increasing trust. Given that most donations occur via mobile devices, special attention is paid to adaptive design. The study aims to develop practical recommendations for creating user-friendly and effective landing pages that enhance donor engagement and improve the success of fundraising campaigns.
Keywords: UI/UX дизайн; благодійний збір